In BMI We Trust: Reframing the Body Mass Index as a Measure of Health - Gutin, Iliya (Soc Theory Health, 2017)
Recent work in medical sociology has provided critical insights into distinguishing between obesity as a condition with severe individual- and population-level health consequences, and obesity as a socially undesirable, stigmatizing construct opposing thinness as the healthy ideal. Less often considered is the role of Body Mass Index (BMI) as the standard by which obesity and healthy weight are measured and defined. Addressing this issue, I begin by distinguishing between BMI as an empirical, objective measure of health, and BMI as an arbitrary, subjective label for categorizing the population. I further consider how BMI is empowered as a measurable quantity through the lens of medicalization and evidence-based medicine, and introduce the “performativity” of BMI as a superior framework for confronting the measure’s conceptual limitations. Emphasizing key parallels between BMI and self-rated health as measures with high predictive validity, yet unspecified mechanisms of action, I propose an epistemological shift away from classifying BMI as a biomarker and toward a more flexible view of the measure as a holistic appraisal of health. In closing, I argue that researchers may continue to leverage BMI’s ease of collection and interpretation, provided they are attuned to its definitional ambiguity across diverse research methods and contexts.